Optimizing Pilgrimage Traditions and Community Empowerment: Integration of Spirituality, Socio-Economy, and Technology in Pilgrimage Practices - Rohanda, Rohanda; Saefullah, Asep; Yunani, Ahmad; Sukmawati, Wati Solihat; Matin, Usep Abdul (Buletin Al-Turas, 2024)
PurposeThis study aimed to explore the optimalization of pilgrimage tradition by integrating social and economic empowerment and the use of technology to enhance spiritual experience, cultural resilience, and their role in strengthening social cohesion. MethodThe study employed a literature review and a theoretical analysis on the concepts of pilgrimage, cultural resilience, and religious tourism in the context of modernization and technology. This study used multi-dimensional approach to analyze the modernization of pilgrimage tradition. Here, this research used the digital technology, while maintaining its spiritual essence and socio-cultural resilience. FindingsThe Findings of the study showed that the pilgrimage tradition and religious tourism can have some contributions. They are empowering local economies through community-based management, strengthening cultural resilience by preserving traditional values, and using technology to improve an accessibility into the quality of spiritual experiences. Additionally, pilgrimage serves as a social interaction platform that fosters harmony in multicultural societies. ConclusionThe optimization of religious tourism supports not only local economic growth, but also cultural preservation, national character building, and the maintenance of social harmony in Indonesia, while preserving its spiritual essence.